2019
DOI: 10.2147/ijgm.s179622
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adherence, satisfaction, and experience with metformin 500 mg prolonged release formulation in Indian patients with type 2 diabetes mellitus: a postmarketing observational study</p>

Abstract: Purpose The aim of this study was to understand patient adherence, satisfaction, and experience with the smaller sized metformin 500 mg prolonged release (PR) tablet that has been manufactured with the help of technological advancement (Gluformin I 500 mg), in comparison with metformin 500 mg extended-release (ER) tablet, in patients with type 2 diabetes mellitus (T2DM). Patients and methods In this postmarketing observational study, T2DM patients who were on a stable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…A study reported slightly better control of blood glucose with homoeopathic treatment compared to conventional treatment, however, it recommended an observation time of more than one year to ascertain the complete effect of treatment [ 21 ]. Only 57.9% of HPs in this study observed proper medication adherence to homoeopathic medicines by DM patients, similar to studies that reported poor compliance with anti-diabetic medication in India [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 85%
“…A study reported slightly better control of blood glucose with homoeopathic treatment compared to conventional treatment, however, it recommended an observation time of more than one year to ascertain the complete effect of treatment [ 21 ]. Only 57.9% of HPs in this study observed proper medication adherence to homoeopathic medicines by DM patients, similar to studies that reported poor compliance with anti-diabetic medication in India [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have reported that compliance with antidiabetic medication in patients in India is poor. 14,15 AYUSH systems of medicine have been used in India for over 2000 years and several cultural groups still utilize them today. However, research into these systems largely remains in the preclinical phase.…”
Section: Discussionmentioning
confidence: 99%
“…Among the included studies, 87 were cohort studies (10,013,130 patients) [42-44,47-57, 59,62,65-74,77,79,83-85,87,89,90,93,95-97,101,105-108,110,112-114,118-126,128-130,133,137, 141-144,148-151,153,154,156-159,161,163-165,167,168,172,174,175,178,179,181], while 69 were cross-sectional studies (28,798 patients) [29][30][31][32][33][34][35][36][37][38][39][40][41]45,46,58,60,61,63,64,75,76,78,[80][81][82]86,88,91,92,94,[98][99][100][102][103][104]109,111,[115][116][117]127,131,132,[134][135][136][138]…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The highest adherence proportion has been found for TZDs (68%, 95% CI: 58-77%), followed by DPP-4i (66%, 95% CI: 56-75%), SGLT-2i (61%, 95% CI: 51-71%), insulin secretagogues (61%, 95% CI: 52-70%), biguanides (55%, 95% CI: 47-64%), and α-glucosidase inhibitors (53%, 95% CI: 36-69%). Most studies investigated adherence to biguanides (30 study-arms) [41,57,59,65,70,71,76,84,85,87,97,99,100,114,118,119,123,128,130,133,136,142,143,146,149,153,159,161,171,172], insulin secretagogues (23 study-arms) [41,43,52,59,65,66,70,71,76,84,97,99,123,128,133,136,142,146,149,159,…”
Section: Stratified Analysesmentioning
confidence: 99%